دور موازنة البرامج والاداء في تحسين الاداء الاستراتيجي للمؤسسات الحكومية (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:              The study aimed to determine the extent to which there are financial, administrative and technological benefits for implementing program and performance budgeting in Iraqi government departments and to know the obstacles facing its application in all their financial, administrative and technological types. To achieve the objectives of the study, a descriptive approach was followed in collecting secondary data from books, scientific journals, previous studies and peer-reviewed research, and a method was followed. Personal interviews and then the inductive and analytical approach in collecting primary data. The results of the study showed that there are expected financial, administrative and technological benefits when applying the budget in a program and performance manner, which lead to preserving public money, reducing the degree of waste, and improving the financial, administrative and technological performance of the Iraqi government. The study recommended preparing rehabilitation, educational and training courses by balancing programs, activities and performance. To qualify administrative and professional cadres to deal with the mechanisms of its implementation, and to seek the assistance of experts, consultants and those with previous experience from countries around the world.